Possibility of Segaliud Lokan Forest Reserve (SLFR), Sandakan As Nature Tourism Attraction - Nurliza Hasmat; Andy Russel Mojiol; Rosmalina Abdul Rashid; Collin Goh; Paul Liau; Sanchez Vincent John; Jesleen Linus (2020)
The tourism sector in Sabah is rapidly developing as the state has high biodiversity resources. The state needs to diversify its natural tourism destinations to increase the number of tourists because tourism is one of the sector that give some contribution to the economic state. Segaliud Lokan Forest Reserve which located in Sandakan district is a newly discovered conservation area that has the potential to be a natural tourism area as this area is rich in biodiversity of flora and fauna as well as attractive landscapes. The objective of the study is to identify the natural resources found in the SLFR that can be the tourist attraction. The Criteria for Assessing Natural Tourism Potential based on National Ecotourism Plan of Malaysia (Guideline for Sabah State) was used in this study. This study shows that the SLFR area has the potential to be a nature tourism attraction but recommends to have some management mechanism in place to precede any development of tourism activity.